THERMAL EFFICIENCY OF GREENHOUSE SOLAR DRYER FOR DRYING STICKY RICE (RD6) AND HEAT TRANSFER MODELING - Piwsaoad, Jagrapan (Life Sciences and Environment Journal, 2024)
This research presents the experimental performance of greenhouse solar dryers and heat transfer modeling of greenhouse solar dryers for drying sticky rice. Five batches of sticky rice were dried; for each batch, we used 5,000 kilograms of sticky rice. The parameters used in the heat transfer model are solar radiation, air temperature, relative humidity and airflow rate. The numerical solution was programmed in C++. The results showed that the moisture content, Root mean square error and determination coefficient ; 0.4741 and 0.9859 respectively. The thermal efficiency of the greenhouse solar dryer was between 24.0%-27.0%. This research presents the experimental performance of greenhouse solar dryers and heat transfer modeling of greenhouse solar dryers for drying sticky rice. Five batches of sticky rice were dried; for each batch, we used 5,000 kilograms of sticky rice. The parameters used in the heat transfer model are solar radiation, air temperature, relative humidity and airflow rate. The numerical solution was programmed in C++. The results showed that the moisture content, Root mean square error and determination coefficient ; 0.4741 and 0.9859 respectively. The thermal efficiency of the greenhouse solar dryer was between 24.0%-27.0%.